Ultrasonic Spectrum Analysis of Granite Damage Evolution Based on Dry-Coupled Ultrasonic Monitoring Technology - Yang Liu; Lan Qiao; Yuan Li; Guodong Ma; Andrei M. Golosov (Advances in Civil Engineering)
The self-developed dry-coupled rock ultrasonic monitoring system is adopted to set up a multidirectional and multiwaveform ultrasonic monitoring network, which aims to analyse the evolution law of acoustic spectrum parameters in the process of granite loading failure under uniaxial compression, to explore the dominant acoustic spectrum characteristic information at different stages of granite loading, and to verify in situ the damage monitoring of time-effect deformation. The results show that the wave velocity, amplitude, and amplitude-frequency of the first wave and the velocity of P-wave and S-wave show a significant upward trend in the rock compaction section. After entering the elastic stage, the three spectral parameters become peacefully stable, and the stage transformation is obvious. In the stable crack growth stage, with the initiation of the crack, the dominant frequency of S-wave shows a significant stage transition compared with the global ultrasonic wave velocity and the first arrived amplitude, and the dominant frequency decreases by 6%. In the unstable crack growth stage, the three acoustic spectrum parameters present obvious downward trend, and the first arrived wave amplitude of S-wave is found to have a significant decline of 39.1%. On the eve of failure, the amplitude-frequency of S-wave shows different feature from the P-wave; that is, S-wave transfers from the state of multipeak in wide frequency to the state of single peak in low frequency, which is the failure precursor of the rock sample.